Tannure MC, Gonçalves AMP. Nursing Care Systematization: A practical guide. 2nd ed. Rio de Janeiro, RJ: Guanabara Koogan; 2010 - Manoel Gomes da Silva Júnior; Lucia Hisako Takase Gonçalves; Marilia de Fátima Vieira Oliveira (Universidade Federal do Ceará, 2014)
This book deals with the establishment of the Nursing Care Systematization, when it addresses administrative tools of computerization and in-service education, considered strategic to the implementation of the Nursing Process, besides dealing with the International Classification of Nursing Practices in Public Health. This piece of work is divided into 16 chapters, which complement the first edition, and at the end of each of them, questions that must evaluate the reader's understanding of the subject were included. Some chapters present case studies that aim to better elucidate what was discussed.